Uji Efek Tonikum Infusa Batang Pasak Bumi dan Campuran Batang Pasak Bumi, Rimpang Jahe Merah dan Buah Cabe Jawa terhadap Mencit Putih Jantan - MELINDA WIDIANINGRUM; - SUHARTINAH; WIWIN HERDWIANI (Fakultas Farmasi Universitas Setia Budi, 2012)
Eurycoma longifolia Jack. stem, Zingiber officinale Rosc. Var. Rubrum rhizome and Piper retrofractum fruits are traditional medicine plants, one of which is to overcome fatigue (tonic). This aim of the experiment was: first to find out whether infuse formula of single Eurycoma longifolia Jack. stem powder and infuse formula of a mixture of Eurycoma longifolia Jack., Zingiber officinale Rosc. rhizome, and Piper retrofractum fruit had tonic effect on male white mouse; the second, to obtain the most effective formula as tonic on for male white mouse. In this study the test animals were divided in 5 groups, and each group consisted of 5 male white mice, i.e. Group 1 F1 was Eurycoma longifolia Jack. stem, group II F2 was a mixture of (2:1:1), group III F3 was a mixture (1:1:1), group IV was positive control (caffeine), group V was negative control (distilled water). The study was conducted by making the orally given male white mice to swim, and then the exhausted times were observed and recorded before and after the treatment. The experiment concluded that first: infusa of single Eurycoma longifolia Jack. stem powder and infuse of a mixture of Eurycoma longifolia Jack., Zingiber officinale Rosc. rhizome, and Piper retrofractum fruit had tonic effect on male white mouse; the second, infuse of formula 3 (1:1:1) to have the best tonicum effect.